Predicion of the functional outcome of cerebral ischemic supratentorial stroke acute period on the basis of spectral analysis of the brain bioelectrical activity - Kuznietsov, A. A. (Zaporozhye Medical Journal, 2018)
The purpose of this study was to determine the most informative parameters of the brain bioelectrical activity spectral analysis for the functional outcome of cerebral ischemic supratentorial stroke (CISS) acute period prediction. Materials and methods. Prospective, cohort and comparative study was conducted among 103 patients in CISS acute period (61 men and 42 women, mean age was 67.7 ± 0.8 years). Electroencephalographic study was conducted on the 2nd–3rd day of the disease with the use of 19-channel electroencephalographic scanner. The values of absolute spectral rhythm power of delta (0.5–4.0 Hz), theta (4–8 Hz), alpha (8–13 Hz), beta (13–35 Hz), theta1 (4–6 Hz), theta2 (6–8 Hz), alpha1 (8–10 Hz), alpha2 (10–13 Hz), beta1 (13–25 Hz) and beta2 (25–35 Hz) bands in the affected hemisphere (AH) and intact hemisphere (IH) were determined. The relative spectral rhythm power (RSRP), fronto-occipital rhythm gradient (FORG) and the severity of interhemispheric rhythm asymmetry (IHRA) were calculated. The functional outcome of the disease acute period was assessed on the 21st day on the basis of the modified Rankin Scale (mRS), while the value of mRS score> 3 was considered as an unfavourable functional outcome. Results. Unfavourable functional outcome of the CISS acute period was registered in 46 (44.6 %) patients. In accordance with the data of multivariate regression analysis it was determined that RSRP of delta band in the IH (OR 95 % CI = 1.31 (1.13–1.52), P = 0.0004), FORG of alpha band in the AH (OR 95 % CI = 29.07 (1.86–455.15), P = 0.0224) and IHRA of alpha band (OR 95 % CI = 0.01 (0.0001–0.80), P = 0.0402) were independently associated with functional outcome of the CISS acute period. The RSRP of delta band in the IH > 18.4 % (Se = 87.0 %, Sp = 87.7 %, AUC 95 % CI = 0.94 (0.87–0.98), P < 0.0001), FORG of alpha band in the AH >-0.066 (Se = 67.4 %, Sp = 70.0 %, AUC 95 % CI = 0.74 (0.65–0.82), P<0.0001) and IHRA alpha band ≤-0.066 (Se = 60.9 %, Sp = 70.2 % AUC 95 % CI = 0.66 (0.56–0.75), P < 0,0039) were the optimal cut-off values as for the unfavourable functional prognosis of CISS acute period. Conclusions. The RSRP of delta band in the IH, FORG of alpha band in the AH and the IHRA of alpha band are the most informative parameters of the brain bioelectrical activity spectral analysis for the prediction of the functional outcome of cerebral ischemic supratentorial stroke acute period.